Altered sarco(endo)plasmic reticulum calcium adenosine triphosphatase 2a content: Targets for heart failure therapy. (July 2018) - Liu, Gang; Li, Si Qi; Hu, Ping Ping; Tong, Xiao Yong
Sarco(endo)plasmic reticulum calcium adenosine triphosphatase is responsible for transporting cytosolic calcium into the sarcoplasmic reticulum and endoplasmic reticulum to maintain calcium homeostasis. Sarco(endo)plasmic reticulum calcium adenosine triphosphatase is the dominant isoform expressed in cardiac tissue, which is regulated by endogenous protein inhibitors, post-translational modifications, hormones as well as microRNAs. Dysfunction of sarco(endo)plasmic reticulum calcium adenosine triphosphatase is associated with heart failure, which makes sarco(endo)plasmic reticulum calcium adenosine triphosphatase a promising target for heart failure therapy. This review summarizes current approaches to ameliorate sarco(endo)plasmic reticulum calcium adenosine triphosphatase function and focuses on phospholamban, an endogenous inhibitor of sarco(endo)plasmic reticulum calcium adenosine triphosphatase, pharmacological tools and gene therapies.